Establishing Correlation of Therapeutic Activity of A Siddha Formulation with its Antioxidant Activity. A Comparative Study - KARTIK CHANDRA PATRA; K. JAYARAM KUMAR (International Journal of Pharma and Bio Sciences, 2010)
Scientific documentation of traditional system of medicine is increasing and need for preparing it for Siddha formulation has become the need of the hour. Amukkara choornam is a popular poly herbal Siddha formulation composed of spices and herbs. It is a most effective formulation used during Gastric troubles, spleen enlargement, leucorrhoea, hiccup, anemia, tuberculosis and kappa diseases. Amukkara choornam samples were collected from different manufacturers of Tamilnadu, India labeled as A, B, C and in house preparation as D. The methanolic extracts of samples were evaluated for their total phenolic content and invitro antioxidant activity by Electrochemical measurement, Total antioxidant capacity (Phosphomolybdenum reduction Assay), Iron (III) to Iron (II) reduction assay, 1, 1’-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging method and Reducing power. In all cases sample-A, B, C and D shows good antioxidant activity but Sample-C shows more activity as compared to other samples.